Improving the education of looked after children: An Aberdeen perspective - Jacinta Birchley; Katrina Stewart (University of Aberdeen, School of Education, 2009)
This article outlines how Aberdeen City Council has taken forward work in relation to improving the educational outcomes for looked after children particularly relating to the role of the designated manager (both in schools and residential units), the critical role of residential child care workers in supporting and promoting education and joint and separate training needs for the key departments involved.